2021
DOI: 10.35371/aoem.2021.33.e33
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical hazardous agent exposure and mental health in the Korean working population: the 5th Korean Working Conditions Survey

Abstract: Background Mental health problems are emerging issues in occupational safety and health, whereas the findings on the relationship between physical hazards and mental health are not consistent. The aim of our study was to investigate the association between physical hazard exposure and mental health outcomes including depression and anxiety. Methods We included 48,476 participants from the fifth Korean Working Conditions Survey (KWCS) in this study. The χ 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Even though these numbers may seem large, compared to the true size of the chemical space, more than 10 60 for organic structures smaller than 500 Da, these lists cover less than 0.001% of the possible chemical space. Furthermore, even for known structures, <1% of them have been experimentally evaluated for their environmental and biological activity (e.g., toxicity), due to the cost and complexities associated with such measurements. In fact, according to Persson et al, around 80% of the chemicals defined as in use according to REACH have yet to be assessed, even though the data may be available . Several studies have shown the negative impact of exposure to chemicals with long-term adverse health outcomes. For example, exposure to per- and polyfluoroalkyl substances (PFAS) has shown to correlate with the symptoms of autoimmune disease as well as mental health issues. , …”
Section: Introductionmentioning
confidence: 99%
“…Even though these numbers may seem large, compared to the true size of the chemical space, more than 10 60 for organic structures smaller than 500 Da, these lists cover less than 0.001% of the possible chemical space. Furthermore, even for known structures, <1% of them have been experimentally evaluated for their environmental and biological activity (e.g., toxicity), due to the cost and complexities associated with such measurements. In fact, according to Persson et al, around 80% of the chemicals defined as in use according to REACH have yet to be assessed, even though the data may be available . Several studies have shown the negative impact of exposure to chemicals with long-term adverse health outcomes. For example, exposure to per- and polyfluoroalkyl substances (PFAS) has shown to correlate with the symptoms of autoimmune disease as well as mental health issues. , …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a large number of studies in this subject have also been focused on the effect on workers’ comfort or psychological effects [ 57 ]. It has been suggested that the psychological and stressful problems created by both noise and whole-body vibration may lead to accidents in professional drivers [ 58 ] and affect the ability to work, leading to reduced physical and mental performance [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Kim et al [ 61 ] detected increased headaches and visual fatigue under the combined effect of noise and vibration in workers. Psychological effects have also been found in workers subjected to HAV and noise simultaneously, such as psychological anxiety and neurological problems [ 62 ], nervous system related disorders [ 63 ], mental health problems such as depression [ 57 ] and insomnia problems [ 64 ], even at levels under the recommended limits by the standards, and they may also lead to other disturbances which, although they might seem less important, cause discomfort to the operator, such as an increased sweating of the hands when handling hand tools in the presence of noise [ 65 ]. Nari et al [ 64 ] revealed an association between occupational noise and vibration exposure and insomnia, both individually and simultaneously.…”
Section: Introductionmentioning
confidence: 99%